Lange practice tests : - Goldberg, Joel S. (McGraw-Hill Medical Publishing Division, 2006)
This resource features thirteen comprehensive practice tests with a total of 650 questions along with many new clinical vignette style questions. The perfect companion to First Aid for the USMLE Step . Completely revised and updated to reflect USMLE Step 1 format.